Vitamin D increases killing of intracellular Leishmania amazonensis in vitro independently of macrophage oxidative mechanisms. Issue 14 (22nd December 2020) - Machado, Patrícia de Almeida; Escrivani, Douglas Oliveira; Gomes, Daniel Claudio Oliveira; Rossi-Bergmann, Bartira; Chaves, Suzana Passos; Coimbra, Elaine Soares; de Matos Guedes, Herbert Leonel
Abstract: Vitamin D has been reported to activate macrophage microbicidal mechanisms by inducing the production of antimicrobial peptides and nitric oxide (NO), but conversely has been shown to contribute to a greater susceptibility to Leishmania amazonensis infection in mice. Thus, this study aimed to evaluate the role of vitamin D during intracellular infection with L. amazonensis by examining its effect on macrophage oxidative mechanisms and parasite survival in vitro . Vitamins D2 and D3 significantly inhibited promastigote and amastigote growth in vitro . Vitamin D3 was not able to induce NO and reactive oxygen species (ROS) production in uninfected macrophages or macrophages infected with L. amazonensis . In addition, vitamin D3 in combination with interferon (IFN)- γ did not enhance amastigote killing and in fact, significantly reduced NO and ROS production when compared with the effect of IFN- γ alone. In this study, we demonstrated that vitamin D directly reduces parasite growth in infected macrophages (approximately 50–60% at 50 μ m ) but this effect is independent of the activation of macrophage oxidative mechanisms. These findings will contribute to a better understanding of the role of vitamin D in cutaneous leishmaniasis.